Quality of life in family members of patients of Schizophrenia and Bipolar Mood Disorder: A crosssectional study in a sample of the Indian population - Patil, Alisha S.; Kale, Sanjiv S. (Nepal Journal of Neuroscience, 2023)
Introduction: Schizophrenia and bipolar disorder are chronic mental diseases with far-reaching effects on those who suffer from them and people who care for them. Family members suffer physical and tremendous emotional distress, often reflected in daily activities and functioning. The quality of life deals with how well a person can do their daily tasks. We have tried to assess the quality of life of family members of people with schizophrenia and bipolar disorder.Materials and Methods: A cross-sectional analysis was performed at a Tertiary Care Centre located in Maharashtra. The research was conducted over the course of six months. After gaining consent, 70 family members of patients diagnosed with schizophrenia as well as bipolar illness were chosen. Sociodemographic data were collected from participants and the quality-of-life instrument (WHO-QoL-BREF) was administered to them. Statistical analysis: SPSS-PC -25 version was used for data analysis. The Shapiro-Wilk test was used to investigate normal distribution. The difference in means between the groups was investigated using student t-test or Mann-Whitney U-test. Statistical differences between supplied proportions was calculated by the chi-square/exact Fisher’s test. Multivariate linear regression analysis was done to see the factors associated with quality of life. Statistics were deemed significant at a P